Negacionismo histórico em pauta: uma proposta de letramento histórico-digital a partir da ditadura civil-militar - Ramos, Gabriel Alves do Carmo Dias (2024)
This main aim of this dissertation is analyzing sensitive stories, focusing on the approach of the Brazilian Civil-Military Dictatorship of 1964, emphasizing the use of digital media in teaching this historical theme to develop the historical-digital literacy of students in a class with high school students preparing for public-military selections in Parnamirim-RN, in the greater NatalRN region. This purpose arose from the perception that this municipality, over the last few years, has been having a strong dialogue with ultra-conservative groups and this correlation expanded some radical effects on the streets of Parnamirin and its classrooms were also affected. The pro-military coup speeches of some students in the classroom and the detection of their routine use of some negationist digital media over time, highlighted a complicated symptom in which significant historical learning could intervene positively. Therefore, the strategy involved the historical reframing of what the Dictatorship of 1964 was, through a historical point of view of digital media that was very different from the previous notion students had. In this way, we have organized a didactic sequence that would provide a counterpoint to the frequent negationist narratives about the coup which circulate online by means of digital information and communication technologies (DICT), emphasizing historical investigation through improving reading, listening, and writing skills of this younger population. In addition to this, a digital booklet and newspaper were created as pedagogical material against falsifying speeches on the topic, serving as support for teachers who, perhaps, want to replicate or adapt these activities in their classes on the Brazilian Civil-Military Dictatorship.